Fuzzy logic system for variable message signs in Kuala Lumpur - Arash Moradkhani Roshandeh, author; Othman Che Puan, author; Majid Joshani, 1982-, author; Eropean Computing Conference (2009 : Tbilisi, Georgia) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL